The Community College in the American Educational System - Cohen, Arthur M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
An analysis is presented of the position of American community colleges in the nation's educational system. First, background is presented on the historical development of the community college; forces contributing to the rise of higher education and the emergence of junior colleges; and the expansion of the role of two-year colleges to include community services and remedial education in addition to transfer, occupational, and postsecondary terminal programs. This section also analyzes forces affecting community college growth over the past four decades, including increased educational access, the student consumerism movement, the increasing enrollment of part-time students, and the absorption by community colleges of the educational functions of other agencies. The next section looks at community college faculty, providing information on their educational background and professional involvement in contrast to their four-year college counterparts; the faculty union movement; and factors such as long working hours and underprepared students which erode faculty job satisfaction. Curriculum and instruction in the community college are discussed next, with particular focus on transfer, occupational, and community service curricula. The paper examines the dilemma faced by college leaders attempting to maintain their institution's place in graded education, while providing a variety of educative services to their constituents on an open-door basis. A number of tables conclude the paper. (LAL)
ERIC Note: Paper prepared for the Study Group on the Condition of Excellence in American Education.
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Education; College Curriculum; College Faculty; College Role; Community Colleges; Community Services; Educational History; Educational Trends; Transfer Programs; Two Year Colleges; Vocational Education; Historical Materials; Opinion Papers; Information Analyses